Looking Askance and Envy - Castelao-Huerta, Isaura (My University, 2023)
This article shows how envy is a form of subtle gender violence within academia. Women professors at the National University of Colombia that participated in this study perceive that they are envied for their academic production within an androcentric system that devalues the knowledge and contributions of women. This occurs in a neoliberal context of scarcity of resources that hinders research and scientific production, but economically stimulates those who produce academic out-put. Thus, the perception of the envy resulting from professional development leads to sinuous relationships among colleagues, leading women professors to self-isolation. At the same time, this also has consequences for their students, since one way of harming the professors is by obstructing the academic progress of people close to them.
Subtle Gender Violence in the Neoliberalised Academia
Keywords: Neoliberalismus; Universität; Kolumbien; Gender Violence